Tandem [4 + 2]/[2 + 2] cycloaddition reactions involving indene or benzofurans and arynes - Bhojgude, Sachin Suresh; Thangaraj, Manikandan; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2014)
The reaction of arynes with indene/benzofurans has been developed. The arynes were generated from 2-(trimethylsilyl)aryl triflates by the fluoride-induced 1,2-elimination react with indene or various benzofurans proceeding via a cascade reaction involving the Diels–Alder reaction and a [2 + 2] cycloaddition reaction. The tandem process afforded functionalized dihydrobenzocyclobutaphenanthrenes in moderate to good yields. Moreover, the method has been utilized for the one-pot synthesis of benzo[b]fluoranthene.

Three-component coupling involving arynes, aromatic tertiary amines, and aldehydes via aryl-aryl amino group migration - Bhojgude, Sachin Suresh; Baviskar, Dnyaneshwar R.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2015)
The transition-Metal-free multicomponent coupling of arynes, aromatic tertiary amines, and aldehydes proceeding via the aryl to aryl amino group migration has been demonstrated. This protocol allows rapid access to ortho-functionalized tertiary amines in moderate to good yields. Moreover, activated ketones can also be used as the aldehyde Component in the present reaction. The similarity of the aryl-aryl tertiary amino group migration with the Smiles rearrangement is striking.